Term-day magnetic observations from the Prague-Clementinum observatory on 1845-06-19 - Pavel Hejda; Miloš Revallo; Fridrich Valach (PANGAEA, 2021)
Data of term-day observations recorded at the Prague-Clementinum observatory in years 1840-1849 are presented. The data were obtained by digitising and processing the original old records published in the yearbooks of this historical observatory. The term-day observations had been agreed for joint measurements by the observatories organised in the Göttingen Magnetic Union (GMU). Data of 120 term-days from January 1840 to December 1849 are published. The observations started at 10 p.m. of Göttingen Mean Time and lasted 24 hours. The interval between observations was 5 minutes (in April, June and July 1842 exceptionally 6 minutes). All time data were transformed into UT, based on the longitude of the Göttingen observatory, which was 9.950°. The time shift is thus 39 extquotesingle48 extquotesingle extquotesingle. The date in the term-day file name indicates the second day which involves substantial part of the observations (22 out of 24 hours).
In: Hejda, P et al. (2021): Data of magnetic storms and term-day observations from the Prague-Clementinum observatory (1839-1849) [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.936921